Strategi Community Based Tourism melalui Pengembangan Wisata Alam dan Budaya Pulau Pari - Alie, Merina; Pratama, Cahya Adhitya; Andhika, Muhammad Restu (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
Indonesia is an archipelagic country that has thousands of islands stretching from Sabang to Merauke. One of them is Pari Island which has high natural potential and is a natural tourist destination that is worth a visit. This study uses descriptive qualitative methods, literature studies and interviews. The purpose of this study is to analyze the Community Based Tourism strategy for the Pari Island tourism sector, especially for natural and cultural tourism. The results of this study with a Community-Based Tourism strategy can improve the community's economy and the youth community becomes active in participating in Pari Island tourism with a note of the need for special handling for the development of Pari island cultural tourism so that it can increase the attractiveness of visits to Pari Island.